Pengembangan Teknologi ERP Untuk Modul Human Resource Management Studi Kasus PT Raja Digital Media - Susanti Susati; Slamet Riyadi (Journal of Computer System and Informatics (JoSYC), 2020)
Human Resources Management is an important instrument for a company in achieving its goals. The use of an integrated information system is an important element for managing business processes in company management. ERP is an integrated information system that is meant in an effort to improve company quality. Especially for online news companies, conventional business process management can affect the quality of performance of the company itself. Focusing on the HRM of the company Berita Online, the study discusses the implementation of human resource management business processes using ERP software, namely Odoo. The research was conducted by analyzing existing business processes and then designing an integrated proposal system and then implementing it into Odoo. The modeling system is designed to optimize data management which is still being processed conventionally. Optimization in every business process improves the quality of security by setting user access rights and the accuracy of data obtained by real-time data transactions, as well as time efficiency, namely reducing the time duration required for recording and storing documents compared to manually.